The Influence of Digital-Based Education on Adolescent Knowledge about BSE - Tavip Indrayana; Heny Prasetyorini; Astuti Salim; Irianto M.Ali; Sunarmi (Sustainable Applied Modification Evidence Community (SAMEC), 2025)
This study aimed to evaluate the effect of a short-duration digital education intervention based on interactive videos distributed through platforms commonly used by adolescents in Semarang. The study used a pre-experimental one-group pretest-posttest design. The results showed that there was a significant difference between the average knowledge score before and after being given digital-based education (p = 0.000). The results of the bivariate analysis showed that digital educational interventions had a positive impact on increasing adolescents' knowledge of early breast cancer detection. The findings of this study are expected to form the basis for developing more effective, applicable, and sustainable technology-based health learning models in the context of an ever-evolving digital landscape. This finding confirms that the use of digital media is an approach that aligns with the characteristics of adolescents and is relevant in improving health literacy related to early detection of breast cancer.